Phytochemical and biological activity screening of the raw extracts of Ficus gul Laut. & K. Schum. var. gul (Family Moraceae) and Palaquium merrillii Dubard (Family Sapotaceae) - Alcancia, Maria Claudia G.
Dichloromethane and methanol extracts of two plant samples namely Ficus gul (Family Moraceae) and Palaquium merrillii (Family Sapotaceae) had undergone screening for phytochemical and other biological activity tests including Brine Shrimp lethality bioassay, agar diffusion assay/Kirby-Bauer method, and serial dilution assay.